Revealing Measles Outbreak Risk With a Nested Immunoglobulin G Serosurvey in Madagascar. Issue 10 (6th June 2018) - Winter, Amy K; Wesolowski, Amy P; Mensah, Keitly J; Ramamonjiharisoa, Miora Bruna; Randriamanantena, Andrianmasina Herivelo; Razafindratsimandresy, Richter; Cauchemez, Simon; Lessler, Justin; Ferrari, Matt J; Metcalf, C Jess E; Héraud, Jean-Michel
Abstract: Madagascar reports few measles cases annually and high vaccination campaign coverage. However, the underlying age profile of immunity and risk of a measles outbreak is unknown. We conducted a nested serological survey, testing 1, 005 serum samples (collected between November 2013 and December 2015 via Madagascar's febrile rash surveillance system) for measles immunoglobulin G antibody titers. We directly estimated the age profile of immunity and compared these estimates with indirect estimates based on a birth cohort model of vaccination coverage and natural infection. Combining these estimates of the age profile of immunity in the population with an age-structured model of transmission, we further predicted the risk of a measles outbreak and the impact of mitigation strategies designed around supplementary immunization activities. The direct and indirect estimates of age-specific seroprevalence show that current measles susceptibility is over 10%, and modeling suggests that Madagascar may be at risk of a major measles epidemic.